Ultrasonography in the Assessment of Lung Recruitment in Patients with Severe Pneumonia - R. Y. Lakhin; E. A. Zhirnova; V. V. Shustrov; S. G. Shulman; A. A. Yemelyanov; B. N. Bogomolov (Неотложная медицинская помощь)
BACKGROUND. Ultrasound study significantly expanded the possibilities of bedside diagnosis in patients with respiratory failure. Using ultrasound, it is possible to determine the volume of lung damage in the form of collapsed alveoli and infiltration areas with preserved airness of the lung tissue. AIM OF STuDY To study the possibility of assessing the recruitment maneuver of the alveoli based on changes in the ultrasound signs of lung tissue damage.MATERIAL AND METHODS. A prospective study was performed in the Clinic of Anesthesiology and Resuscitation of S.M. Kirov Military Medical Academy. The study included 36 patients who were treated in the period from 2010 to 2017 with a duration of respiratory support of at least 48 hours and oxygenation index less than 300 mmHg. For 36 patients, 48 alveoli recruitment maneuvers were performed according to a step-by-step method under the control of dynamic compliance and average tidal volume. Ultrasound determined the type and extent of destruction of lung tissue by signs of infiltration and consolidation.RESULTS. In the studied patients, after carrying out a maneuver of recruitment of the alveoli, arterial blood oxygenation indices increased statistically significantly, PaCO2 level decreased, pulmonary tissue compliance improved, respiratory volume grew. All this confirmed the mobilization of the alveoli and improved lung ventilation. Ultrasonographic evaluation of lung tissue showed a significant decrease in the severity of the ultrasound sign of infiltration after recruitment maneuver from 46.5 (38; 57.5) to 37.5 (30.5; 49.5). However, recruitment had practically no effect on the volume of the consolidated area of lung tissue: the general consolidation index before (4 (3; 5)) and after (4 (3; 5)) the maneuver had no statistically significant differences.CONCLUSIONS. The pneumonia-affected consolidated lung tissue has a low recruitment potential and the volume of consolidation does not change with the growth of PEEP. After the recruitment maneuver, the number of B-lines decreases, indicating a decrease in infiltration and an increase in lung airness.Authors declare lack of the conflicts of interests.